Collaborative Solutions: Leveraging Artificial Intelligence for Resilient Agriculture, Energy, and Risk Systems in Africa - African Climate Policy Centre; Accelerating Impacts of CGIAR Climate Research for Africa; United Nations Office for Disaster Risk Reduction (2025)
This mandated session was centered on the use of Artificial Intelligence (AI), Earth Observation (EO), and material innovation to enhance climate resilience in Africa. The primary focus was on African-led innovation, ethical use, and South-South cooperation for the achievement of scalable, context-appropriate solutions in agriculture, energy, and disaster/climate risk management. The main takeaways are: • Materials innovation, EO, and AI offer game-changing possibilities for precision farming, renewable energy optimization, disaster risk reduction, and resilient infrastructure. • Africa should transition from passive technology recipient to co-creator, but success depends on human capital, inclusive governance, ethical standards, financing, and continental collaboration. • Youth engagement, citizen-centric approaches, and locally grounded co-creation are critical for equitable deployment. • South-South and intra-African cooperation provide replicable models for scaling, knowledge sharing, and avoiding duplication. The session also generated actionable proposals on finance, governance, ethical use of AI, and energy transition, with concrete next steps to deploy AI and EO solutions at the continental level.